Solar light driven photochromic membranes with viologen additives in PVDF/PVP matrix - Tohtayeva, Jahan; Altınışık, Sinem; Akgün, Mert; Uğur Nigiz, Filiz; Koyuncu, Sermet (Frontiers in Materials, 2024)
This study explores the synthesis and characterization of photochromic Polyvinylidenefluoride/Polyvinylpyrrolidone (PVDF/PVP)-based membranes, prepared through an in situ thiol-ene click reaction by incorporating viologen derivatives with different counter ions. Viologens are well-known for their light-sensitive properties and ability to change color, making them useful in various optoelectronic applications. The membranes developed in this study exhibit significant improvements in their interactions with light as a result of improved morphology and enhanced ionic conductivity (≈4 × 10−4 S cm–1) with higher porosity (Ra: 11.26–33.76 nm) compared to conventionally prepared membranes. These membranes show the ability to block almost all ultraviolet (UV) and a 90% of visible light after irradiation. Thanks to these properties, the membranes undergo visible color changes when exposed to sunlight, making them suitable for photochromic and thermochromic applications. The findings of this study could contribute to the development of innovative coating materials that enhance energy efficiency, potentially being applied to buildings, automotive windows, and other surfaces.